Static permeability assessment method to distinguish brain tumour recurrence from pseudoprogression. (15th October 2021) - Tsang, Kai; Pang, Chun; Butler, Sam
Abstract: Aims: It is common to have adjuvant chemo-radiotherapy after primary brain tumour resection. It is a known side effect that enhancing lesion could be seen in radiation territory after treatment, termed as pseudoprogression. It has been a difficult task to distinguish brain between tumour recurrence from pseudoprogression after radiotherapy. Timing of occurrence of these can overlap. It is important to distinguish the two as management is completely different. Early intervention in recurrence could improve survival time while pseudoprogression could be self-limiting. Surgical resection of pseudoprogression could be counter-productive. The radiological approach has been relying on multimodality investigation and close follow up. It has come to our institution notice that there is a new technique which could distinguish the two conditions efficiently. That's static permeability assessment method, also known as treatment response assessment maps (TRAMs). Our experience with it so far has been beneficial. Method: This is a retrospective case series review of primary brain tumour treatment in our neurosurgical institution in 2020. Two high resolution 3D T1-weighted brain MRI images were acquired after a standard dose of gadolinium based contrast agent was injected. The first acquisition began five minutes after injection, and the second began 60 – 105 minutes post contrast injection. The TRAMs technique is based on image subtraction that is post processed after acquisition. The resultant subtracted image set was mapped to grey scale values, where voxels showing contrast clearance were light grey/white, and those showing contrast accumulation were dark grey/black. The zero value (i.e. no clearance or accumulation) was therefore mid-grey. Those with contrast clearance is associated with tumour recurrence. TRAMs images were compared to serial follow up imaging and histopathology results to determine the diagnostic accuracy of the technique. Results: We have identified 21 patients in this period who had concern of either of pseudoprogression or tumour recurrence/progression. There were 6 females and 15 males, mean age 51. There were 14 glioblastoma multiforme (GBM), 5 astrocytoma, 1 oligodendroglioma and 1 post radiotherapy arteriovenous malformation. 17 cases were found to have clear cut recurrence, pseudoprogression or mixture of both in TRAMS. These findings are backed up by histology or repeated follow up scan. 4 cases were considered as equivocal. In retrospect, these cases have challenging interpretation due to poor case selection. TRAMs could distinguish high grade transformation as well as detecting recurrence. In some difficult cases, it is found that both pseudoprogression and recurrence could happen together. Conclusion: TRAMs is a useful adjunct to the multimodalities of diagnostic techniques in tricky situation. This has provided an efficient and easy to use tool for radiologists to come up with the answer. We are the first independent centre to report on this technique. This is still early days and fine-tuning of its use is still undergoing. It is clear this has saved precious resources and has given patients more suitable care. We think it would be beneficial for us to share our experience with others and hope to get future collaboration with other centres.